Startup Culture as a Masculinity Contest: An Exploratory Study on Prevalence and Gender Dynamics - Berit Sandberg (Social Sciences)
Startups are often praised for their innovative power and dynamic work environments, but are also criticized for workplace cultures that perpetuate traditional masculine norms of competitiveness, workaholism, emotional resilience, and strength. This exploratory study examines the prevalence of Masculinity Contest Culture (MCC) in German startups and related gender dynamics. The Masculinity Contest Culture scale, which assesses masculine norms related to emotional resilience, physical superiority, workaholism, and aggressive competitiveness, was employed to collect data from 101 participants representing various startups. The results indicate an overall low prevalence of MCC, with slightly higher scores for strong commitment to work. Individuals from disparate gender and hierarchical status groups exhibited comparable ratings of the intensity of toxic masculinity. While the presence of female founders and supervisors did not affect MCC scores, male dominance within the work environment had a small but significant amplifying effect. Significant differences were observed based on the prevailing leadership style, indicating that a shared leadership approach is associated with the creation of a more inclusive and less toxic work environment. The results challenge commonly held assumptions about tech startups. In addition, the study highlights the need for further research into the impact of leadership dynamics on startup culture.